Effectiveness of Aerator Ventures, Deposition with Magnets, Filtering, and Ion Exchange in One Unit against Reduction of Iron, Total Dissolved Solid, and Marine Well Water - Sudiarto, Dwi; Nurhayati, Nurhayati; Fajriansyah, Fajriansyah (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: It is known the effectiveness of a venturi aerator, deposition with a sand filter magnet and ion exchange in one unit to reduce Fe content, total dissolved solid (TDS) and saltiness (CL content) in clean water, and the ability of ion exchange to reduce CL content is known. AIM: This study aims to analyze the effectiveness of venturi aerator, magnetic sedimentation, filtration, and ion exchange in one unit against Fe, TDS, and CL well water. METHODS: The method used is a quasi-experimental method using aeration with a venturi system, deposition with magnets, filtration, and ion exchange. The population in this study was all water containing Fe and CL in the Darul Kamal sub-district, Aceh Besar. The sample in this study is part of the population following research needs. RESULTS: The results showed an effect of a venturi aerator, deposition with magnets, filtering sea sand, anion, and cation resins in one unit to decrease Fe content and did not affect decreasing TDS content and Salinity. Moreover, a venturi aerator has an effect, deposition with magnets, filtering sea sand, anion, and cation resins in one unit on the decrease in Fe content, TDS, and salinity at deposition time of 24 h. Venturi aerator’s effect on Fe reduction does not affect TDS and CL of well water. There is an effect of venturi aerator and precipitation with magnets, in one unit on Fe reduction, and does not affect TDS and CL of well water. There is an effect of venturi aerator, precipitation with magnets, filtration in one unit on Fe reduction, no effect on TDS, and CL of well water. CONCLUSION: This tool effectively reduces Fe content and effectively reduces Fe, TDS, and salinity at a 24 h deposition time.